On the understanding of the current status of urban air mobility development and its future prospects: Commuting in a flying vehicle as a new paradigm. (October 2022) - Pons-Prats, Jordi; Živojinović, Tanja; Kuljanin, Jovana
Abstract: Urban Air Mobility (UAM) has the potential to disrupt air transportation, providing disruptive innovation not only to aviation but also to mobility systems and urban planning. Underpinned by technological advances in batteries, as well as in electric and distributed propulsion that facilitate the design of novel aircraft types with the capability for Vertical Take-off and Landing (VTOL), the UAM is attracting the attention of an extensive list of stakeholders, institutions and companies. It also covers a broad range of different areas of interest that have to be considered by a holistic and multidisciplinary approach in order to derive its full potential. This paper aims to provide an in-depth qualitative analysis of relevant aspects of UAM development and implementation. The added value of this paper is in assessing the current status and prospects of the most important UAM areas by analysing them from the literature and practice point of views. The paper also deals with the main challenges and multidisciplinary constraints that might slow down the pace towards the successful application of the subject concept. Highlights: The UAM concept reasonably attracts a lot of attention from various stakeholders. Integration of UAM into existing transportation systems is one of the major tasks. Societal impacts and public approval have great importance for the UAM implementation. Technology and regulations progress is fast due to the large interest for the UAM. Air Traffic Management will be a challenging mission in the UAM concept.